2016
DOI: 10.1038/mtna.2016.94
|View full text |Cite
|
Sign up to set email alerts
|

Long Intergenic Noncoding RNA 00511 Acts as an Oncogene in Non–small-cell Lung Cancer by Binding to EZH2 and Suppressing p57

Abstract: Long noncoding RNAs (lncRNAs) play crucial roles in carcinogenesis. However, the function and mechanism of lncRNAs in human non–small-cell lung cancer (NSCLC) are still remaining largely unknown. Long intergenic noncoding RNA 00511 (LINC00511) has been found to be upregulated and acts as an oncogene in breast cancer, but little is known about its expression pattern, biological function and underlying mechanism in NSCLC. Herein, we identified LINC00511 as an oncogenic lncRNA by driving tumorigenesis in NSCLC. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
177
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(186 citation statements)
references
References 51 publications
9
177
0
Order By: Relevance
“…And the aberrant methylation such as PRC2-mediated histone methylation in the CKI gene promoter region is associated with gene expression suppression [36-39]. Additionally, plenty of lncRNAs have been reported to modulate specific genetic loci through recruiting PRC2 and PRC2-mediated epigenetic regulation play important role in tumorigenesis [17, 30, 31, 40-42]. In present study, our finding demonstrated that the deletion of SNHG6 could epigenetically silence the expression of p27 through interacting with EZH2.…”
Section: Discussionmentioning
confidence: 99%
“…And the aberrant methylation such as PRC2-mediated histone methylation in the CKI gene promoter region is associated with gene expression suppression [36-39]. Additionally, plenty of lncRNAs have been reported to modulate specific genetic loci through recruiting PRC2 and PRC2-mediated epigenetic regulation play important role in tumorigenesis [17, 30, 31, 40-42]. In present study, our finding demonstrated that the deletion of SNHG6 could epigenetically silence the expression of p27 through interacting with EZH2.…”
Section: Discussionmentioning
confidence: 99%
“…The highly complex nature of lncRNAs indicates that these are key regulators in cellular process and tumor progression. LncRNAs have been identified as potential biomarkers and therapeutic targets for human cancers . However, the mechanisms by which lncRNAs are transcriptionally regulated and their roles in HCC progression have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…This regulatory mechanism is very beneficial for the body/cell to generate feedback and regulation based on external signals and stimuli. lincRNA00511 acts as a modular scaffold of EZH2/PRC2 complexes, coordinating their localization, and regulates histone modification patterns of target genes, including p57, consequently altering tumor cellular biology …”
Section: Introduction Of Lncrnasmentioning
confidence: 99%